INDEKS NUTRISI DAN KESINTASAN LARVA SPODOPTERA LITURA F. YANG DIBERI PAKAN MENGANDUNG EKSTRAK KULIT JENGKOL (PITHECELLOBIUM LOBATUM BENTH.) - Trisnowati B. Ambarningrum, Hery Pratiknyo, dan Slamet Priyanto . (Universitas Lampung, 2009)
Nutrition indices and survivorship of Spodoptera Litura F. larvae is fed nutrition including jengkol bark extract (Pithecellobium Lobatum Benth). The effect of P. lobatum barks extract on nutrition indices and survivorship S. litura larvae has been investigated. Nutrition indices were observed by giving fifth-instar larvae one of the three diets, every group of diet was added various concentration of barks extract, containing either 1.10; 2.20; or 4.40%. Survivorship were observed by giving first-instar larvae one of the three diets, every group of diet was added various concentration of barks extract, containing either 0.6; 1.2; or 2.4%. The result showed that, the Relative Consumption Rate (RCR), Relative Growth Rate (RGR), Efficiencies of food use (ECD and ECI) value of larvae treated were significantly lower in the case of treated larvae than that of the controls, Approximate Digestibility (AD) value of larvae treated were significantly higher in the case of treated larvae than that of the controls and decrease of survivorship tested larvae.